Modul Berbsis Green History untuk Pembelajaran Sejarah di Sekolah Menengah Atas - Elfa Michellia Karima; Firza Firza (Diakronika, 2018)
The important thing in studying history is to make it more interesting. The teacher as a facilitator must find other ways to make student interested when they learn, so far history learning is less exciting because student are obligated to remember the fact of historical events. Green history-based module learning will provide more interesting learning material for students to understand history since the module integrates paste vents whic hare related to the presentand also witht hesurrounding environment. The purpose of this researc histoimprove students knowledge, skills, and awareness about environmental values andenvironmental issues. This research is development research, which some stages namely Data Collection, Model Design, Design Validation, Design Revision, Product Trial, Product Revision,Mass Production of Products. This research has a positive impact on students in learning history, students understanding increases and students can analyse a historical event.